Modelling detention basins measured from high‐resolution light detection and ranging data - Wang, Lei; Yu, Jaehyung (Hydrological processes, 2012)
The construction of stormwater detention basins is a best management practice to effectively control floods, to provide additional surface storage for excess floodwater and to compensate for the adverse effects of urban development. Traditional field‐based levelling survey methods are very time consuming and subject to human‐induced arbitrariness and error. This article presents an approach to modelling detention basins measured from light detection and ranging remote sensing data. A case study is illustrated by using the White Oak Bayou watershed of Harris County, Texas. The storage–stage curve obtained from the volumetric analysis is used in a modified detention basins routing model, which was developed by adding the weir structure control to the traditional hydrologic reservoir routing equations. The model simulation showed that the peak flow of the synthetic 100‐year reoccurrence event was effectively reduced and delayed by the detention basins. The comparison with the simulation results from the traditional reservoir routing model suggested that previous studies using the reservoir routing model were likely to underestimate the flood reduction effect of detention basins. The sensitivity analysis of the parameters showed that the detention basin design and evaluation should pay more attention on the weir height and river channel's roughness. Copyright © 2011 John Wiley & Sons, Ltd.